Lean Healthcare: barreiras e caminhos estratégicos para superá-las - Codognotto, Emanuela Leal (Universidade Federal de São Carlos, 2026)
The pursuit of efficiency and quality in healthcare has led hospitals to adopt continuous improvement practices inspired by the industrial sector, such as Lean Healthcare (LH). However, organizations still face several challenges that hinder its successful implementation. This research aimed to understand the relationship between the main barriers to LH implementation and the strategic pathways to overcome them. The study adopted a mixed-methods approach, combining a Systematic Literature Review (SLR) and Content Analysis, which identified 14 strategic means related to ten main barriers, with Interpretive Structural Modeling (ISM) and MICMAC analysis, employed to map the relationships of dependence and interdependence among the factors. The results enabled the development of a comprehensive four-level framework, representing the logical progression from foundational conditions to sustainable LH outcomes. The study contributes to theory by integrating qualitative and quantitative approaches through the lens of Organizational Learning Theory, offering a hierarchical view of barriers and strategies to overcome them. From a practical perspective, it provides a structured roadmap for hospital managers to prioritize actions and strengthen organizational learning within their Lean initiatives. The originality of the research lies in the integration of ISM–MICMAC methodologies with learning theory, resulting in an innovative model to promote the sustainability of Lean Healthcare.
Lean Healthcare: barriers and strategic pathways to overcome them
Keywords: Lean Healthcare; Barriers; Organizational Learning; Framework; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO::GARANTIA DE CONTROLE DE QUALIDADE; 3. Saúde e Bem-Estar; 8. Trabalho Decente e Crescimento Econômico